Real-World Outcomes of Allogeneic Immunosafe Plasma Rich in Growth Factors Eye Drops for Refractory Ocular Surface Diseases: A Prospective Observational Study - Rosa Alvarado-Villacorta; Jesús Merayo-Lloves; Ronald M. Sánchez-Ávila; Belén Alfonso-Bartolozzi; Carlos Lisa; Luis Fernández-Vega-Cueto; José F. Alfonso; Eduardo Anitua (Ophthalmology and Therapy)
Abstract Introduction Immunosafe plasma rich in growth factors eye drops (is-ePRGF) have shown anti-inflammatory and regenerative effects on ocular surface diseases (OSD). However, medical or technical issues may preclude some patients from undergoing autologous blood extraction. We aimed to evaluate the safety and clinical outcomes of allogeneic is-ePRGF therapy for refractory OSD in real-world practice. Methods A single-center cohort was conducted involving consecutive patients with severe OSD nonresponsive to conventional therapy. All participants received allogeneic is-ePRGF derived from healthy family donors as compassionate treatment (one drop four times daily for 6 weeks per cycle), with a minimum follow-up of 3 months. Primary outcomes included symptom changes assessed by Ocular Surface Disease Index (OSDI) and Symptom Assessment iN Dry Eye (SANDE) questionnaires, resolution of persistent epithelial defects (PED), and adverse events (AE). Secondary outcomes included best-corrected visual acuity (BCVA), intraocular pressure (IOP), corneal staining, Schirmer I test, tear break-up time (BUT), conjunctival bulbar redness, and meibomian gland dysfunction (MGD). Multilevel mixed-effects models were used to account for intra-patient and inter-eye correlations. Results A total of 30 patients (58 eyes; mean age 53.4 ± 22.6 years; 50% female) were included. The most common diagnoses were severe dry eye disease and neurotrophic keratopathy, frequently associated with autoimmune/inflammatory conditions. Overall, 12 patients (40%) had previously received autologous therapies. Donors were primarily first-degree relatives. Median follow-up was 9 months (range 3‒30 months), with a mean of 6.2 ± 3 cycles. OSDI and SANDE scores significantly improved (p < 0.001). Among 12 cases with PED, 8 (67%) fully resolved. No AE occurred. BCVA (p = 0.010), Schirmer test, BUT, conjunctival bulbar redness, corneal staining, and MGD severity improved significantly (p < 0.001); IOP remained stable (p = 0.132). Conclusions Allogeneic is-ePRGF was a safe and effective alternative for refractory OSD when autologous sources were not available or suitable. Standardization of regulatory frameworks for allogeneic blood-based therapies is needed to support broader clinical adoption.